A critical analysis of current debates in natural law: a theo-cultural engagement with John Finnis, Jean Porter, & John Milbank - Morgan, G (2021)
This thesis argues that natural law – when construed as an epistemological and trans-cultural lingua franca, adjudged capable of legitimating the rational intelligibility and universal applicability of specific Christian moral principles within contemporary “secular” discourse – has failed. Through a detailed analysis of the contributions of three prominent natural law theorists who are located within a shared philosophical-theological tradition, namely, John Finnis, Jean Porter, and John Milbank, the thesis illuminates the extent to which this failure is as much intramural as it is extramural. The contribution of this thesis is borne out of a two-fold realisation: (1) that despite renewed levels of inter-disciplinary interest within the academy, the discourse has become increasingly fragmented and will continue to fragment in the absence of a critical analysis of the deeper theo-cultural assumptions and aporias that animate current debates in natural law; (2) that by illuminating and attending to the theological and methodological “unsaid(s)” that have, heretofore, been seldom acknowledged, one can begin to appreciate how the fragmentation of the discourse is inexorably linked to the fragmentation of the secular mythos. Once this two-fold realisation has been critically substantiated, the thesis develops its contribution to knowledge by exploring how new horizons open up for natural law if the theological “unsaid(s)” are allowed to surface and the disremembering power of the secular mythos is overcome. The thesis addresses one such horizon as a gateway to further research — that the theoretical fulcrum of the natural law lies not in its perceptual self-evidence or in its immanent secularity; but rather in its subtle provision of an immanent eschatology. This insight not only provides an immanent critique of current debates in natural law but is also theologically generative and subversive. More specifically, I argue that natural law is a theory of dialogical anamnesis — a “work of memory”.